A Passage Repeated - Fitzsimons, Connie; Long Beach Museum of Art, Long Beach (Long Beach : Long Beach Museum of Art, 1985)
Barry, Judith ; Gerson, Barry ; Hall, Doug ; Hoberman, Perry ; Hoover, Nan ; Kuntzel, THierry ; Lundberg, Bill ; Sharits, Paul
A Passage Repeated, Long Beach Museum of Art, Long Beach, September 18 - November 3, 1985
boek